A Rare Case of Mitochondrial Neurogastrointestinal Encephalomyopathy. Issue 5 (9th May 2022) - Manski, Scott Adam; Adkins, Christopher; Smith, Colin; Blair, Brian
ABSTRACT: Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare autosomal recessive disease due to mutations in the thymidine phosphorylase gene, leading to mitochondrial alterations and dysfunctions in oxidative phosphorylation. MNGIE is a multisystem disorder with gastrointestinal symptoms arising in large part from gut dysmotility and neurological manifestations including peripheral neuropathy. We discuss a patient with chronic vomiting, diarrhea, and weight loss with a prior unrevealing extensive workup who was hospitalized for severe protein-calorie malnutrition. The patient was found to have gastrointestinal dysmotility on a gastric emptying scan and persistently elevated lactate levels and was subsequently diagnosed with MNGIE after confirmatory testing.